RESPONS KUMBANG AMBROSIA TERHADAP PERLAKUAN DENG AN PESTISIDA - Paimin Sukartana; Abdurahim Martawijaya; Dominicus Martono (Jurnal Penelitian Hasil Hutan (Journal of Forest Products Research), 2017)
A  case study   on  the  behavioral  responses  of  ambrosia  beetles  to some  pesticidal  formulations   was carried out  at  a logging area in West Kalimantan  in 1981.    Each  pesticide  formulation   was sprayed  to debarked  logs of fresh1%  felled  ramin trees  (Gonystylus bancanus Kurz.}.   The  tested   logs  were,  then,  allowed  for  the  beetle  infestations for  four  weeks,   and inspections  were conducted   weekly  to count  the beetle  tunnels. A  lower  intensity   of  the  beetle   infestation   on  the  treated  logs  than  those  on  the  controls   was  considered  as an inhibitory   response.  in contrast,   a  higher  intensity   of  the  infestation   on  the  treated  logs  was  indicatively   caused  by  a stimulatory    response.